Analitycal Hierarchy Process Untuk Menganalisa Faktor Pemilihan Web Browser Pada Desktop - Mustika, Wida Prima; Mardian, Mardian; Rinawati, Rinawati (STIKOM Tunas Bangsa Pematangsiantar, 2018)
Convenience in using the internet is strongly influenced by the web browser used. Web browser is an application to be able to surf the internet, which serves to display and interact with the server. The development of the internet and the increasing number of website are there, make the internet as the primary source of information. With options and advantages possessed by each web browser, internet users often do not make the most of the features provided. It is that makes the background of how to apply the research methods Analytical Hierarchy Process (AHP) for choosing a web browser on the desktop. This research aims to create a decision support system for internet users in selecting the appropriate web browser criteria and requirements.